Multifunctional electrochemical biosensor with "tetrahedral tripods" assisted multiple tandem hairpins assembly for ultra-sensitive detection of target DNA. Issue 33 (4th June 2021) - Huang, Yuqi; Zhao, Shuhui; Zhang, Wenxiu; Duan, Qiuyue; Yan, Qi; Fu, Hu; Zhong, Liang; Yi, Gang
Abstract : Schematic illustration of the fabricated electrochemical biosensor. TTs assisted multiple tandem hairpins assembly for ultra-sensitive detection of target DNA. Abstract : Nucleic acids are genetic materials in the human body that play important roles in storing, copying, and transmitting genetic information. Abnormal nucleic acid sequences, base mutations, and genetic changes often lead to cancer and other diseases. Meanwhile, methylated DNA is one of the main epigenetic modifications, which is considered to be an excellent biomarker in the early detection, prognosis, and treatment of cancers. Therefore, a multifunctional electrochemical biosensor was constructed with sturdy tetrahedral tripods, which assisted multiple tandem hairpins through base complementary pairing and effective ultra-sensitive detection of targets (DNA, microRNA, and methylated DNA). In the experiments, experimental conditions were optimized, and different DNA concentrations in serum were detected to verify the sensitivity of the biosensor and the feasibility of this protocol. In addition, microRNA and DNA methylation were detected through different designs of tetrahedral tripods (TTs) that capture probes to prove the superiority of this scheme. A sturdy pyramid structure of TTs extremely enhanced the capture efficiency of targets. The targets triggered the one-step isothermal multi-tandem amplification reaction by incubating multiple hairpin assemblies. To our knowledge, a combination of two parts, which greatly reduced background interference and decreased non-specific substance interference, has appeared for the first time in this paper. Moreover, the load area of electrochemical substances was significantly increased than that in previous studies. This greatly increased the detection range and detection limit of targets. The electrochemical signal responses were generated in freely diffusing hexaammineruthenium(iii ) chloride (RuHex). RuHex could adhere to the DNA phosphate backbone by a powerful electrostatic attraction, causing increased current responses.